Four Views on Christian Spirituality - Nassif, Bradley; Demarest, Bruce A. (Grand Rapids, Mich. : Zondervan, 2012)
Four Views on Christian Spirituality presents, in the words of learned proponents, the aims and emphases of four major traditions of Christian spirituality: Eastern Orthodoxy, Roman Catholicism, Evangelicalism, and Liberal Protestantism. General editor Bruce Demarest includes critiques of each tradition by opposing contributors, providing a useful resource for further discussion and study. --from publisher description
Orthodox spirituality: a quest for transfigured humanity / Bradley Nassif -- 'Come to the father': the fact at the foundation of Catholic spirituality / Scott Hahn -- The progressive face of mainline protestant spirituality / Joseph Driskill -- Evangelical spirituality / Evan Howard.
Includes bibliographical references and indexes.
Keywords: Spirituality - Four View; Spirituality - Foundation